Hypodense regions in the peripapillary region increased the risk of macular retinoschisis detected by optical coherence tomography - She, Xiangjun; Zhou, Congying; Liang, Zhi; Xie, Jin; Zhao, Shixin; Tao, Jiwei; Zhang, Yun; Mao, Jianbo; Chen, Yiqi; Shen, Lijun (Frontiers in Medicine, 2022)
Purpose: To investigate the clinical features of peripapillary regions in patients with myopic macular retinoschisis and its association with development of retinoschisis (MRS). Methods: Cross sectional study, highly myopic patients with or without MRS were recruited in the study, hypodense regions were analyzed in the peripapillary regions. The vitreoretinal adhesions around macular, paravascular were compared between groups. The risk factors for development of MRS was analyzed by regression. Results: Of 88 myopic eyes, MRS was detected in 45 eyes (51%), The eyes with MRS showed a higher rate of peripapillary retinoschisis and paravascular retinoschisis (P < 0.001, P = 0.006). Hypodense regions were detected in 25 eyes (20.35%). Higher rate of horizontal and vertical macular MRS were detected in hypodense group (P=0.012, P = 0.002). Lower refractive error, longer axial length, higher rates of outer retinoschisis both in horizontal and vertical macular were observed in hypodense group(P = 0.012, P = 0.006, P = 0.038, P = 0.034). Higher rates of inner, outer retinoschisis, vitreoschisis and microfolds along superior vascular arcade were detected in hypodense group (P = 0.005, P = 0.001, P = 0.014, P=0.014). Higher rates of ILM detachment, inner RS, outer RS were detected along inferior vascular arcade in hypodense group (P=0.008, P=0.001, P=0.028). Hypodense regions, axial length and PICC were significantly correlated with severity of macular retinoschisis Conclusions: The hypodense regions were likely to effect outer retinoschisis both in macular and paravascular regions. It was a risk factor for development of MRS.